Mindfulness and its implications for anxiety and stress management - Fatemi, Sayyed Mohsen (Henry Stewart Talks, 2019)
Types of mindfulness, Information processing and mindfulness, Mindfulness approach to solve personal challenges, Mindfulness approach to anxiety and stress